Requirement of the Drosophila raf homologue for torso function. - Ambrosio, L.; Mahowald, A.P.; Perrimon, N. (Nature, 1989)
In Drosophila the correct formation of the most anterior and posterior regions of the larva, acron and telson is dependent on the maternally expressed terminal class of genes. In their absence, the anterior head skeleton is truncated and all the structures posterior to the abdominal segment seven are not formed. The protein predicted to be encoded by one of these genes, torso (tor), seems to be a transmembrane protein with an extracytoplasmic domain acting as a receptor and a cytoplasmic domain containing tyrosine kinase activity. Here we report that another member of the terminal-genes class, l(1)polehole (l(1)ph), which is also zygotically expressed, is the Drosophila homologue of the v-raf oncogene and encodes a potential serine-and-threonine kinase. We also show that functional l(1)ph gene product is required for the expression of a gain-of-function tor mutant phenotype, indicating that l(1)ph acts downstream of tor. Together, these results support the idea that the induction of terminal development occurs through a signal transduction system, involving the local activation of the tor-encoded tyrosine kinase at the anterior and posterior egg poles, resulting in the phosphorylation of the l(1)ph gene product. In turn, downstream target proteins may be phosphorylated, ultimately leading to the regionalized expression of zygotic target genes. Such a process is in agreement with the finding that both tor and l(1)ph messenger RNAs are evenly distributed.